2011 IEEE Congress of Evolutionary Computation (CEC) 2011
DOI: 10.1109/cec.2011.5949861
|View full text |Cite
|
Sign up to set email alerts
|

An abstract representation model for evolutionary analysis of multi-agent interactions

Abstract: Abstract-Intelligent agents are able to assist human in managing highly dynamic and complex systems in various knowledge intensive domains. The communication between different agents interacting in an integrated multi-agents system can be managed through a set of steering rules, which together form interaction protocols. To support the negotiation, communication and interaction between different intelligent agents, using an appropriate knowledge representation formalism is crucial. This paper introduces the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, the difference between perceived importance and received support were statistically significant for four dimensions of parental support [3]. In another study, it was also shown that the parents of premature infants, especially mothers, experience higher stress in the NICU [29], and the stressors were factors that can cause stress and worry in parents. Therefore, their need for social support is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the difference between perceived importance and received support were statistically significant for four dimensions of parental support [3]. In another study, it was also shown that the parents of premature infants, especially mothers, experience higher stress in the NICU [29], and the stressors were factors that can cause stress and worry in parents. Therefore, their need for social support is essential.…”
Section: Discussionmentioning
confidence: 99%
“…As shown category theoritical approach has been used to perform change management in bio-ontologies by defining categories of Class,States, Ontologies and Opearation to analyze ontological changes at both internal and external levels. Also categories of Agent, MAS,Services, Rules and Preposition have been used to formalize agents interactions and negotiation [28]. Moreover categorical representation has been employed as a main formal method for performing hierarchical distributed graph transformation, specifically through two categories of GRAPH and DGRAPH (distributed graphs).…”
Section: Changes In Biomedical Ontologiesmentioning
confidence: 99%